PSYCHOLOGICAL CONDITION OF LECTURERS AND EDUCATION STAFF BEFORE THE IMPLEMENTATION OF THE COVID-19 VACCINATION - Ratih Christiana; Ibnu Mahmudi; Suharni Suharni; Lela Fitri Murni Cayanti (Proceeding International Conference on Digital Education and Social Science, 2022)
This article aims to conduct research to determine the psychological condition of lecturers and academic employees prior to the implementation of the covid-19 vaccination. The respondents of this study consisted of 126 lecturers and academic staff who worked at the University of PGRI Madiun. The instrument format is an open questionnaire compiled in the form of a google form called a questionnaire before the Covid-19 Vaccine Immunization, with cognitive, affective and conative aspects. The research method uses a qualitative narrative method with the selection of cases of maximum variation, testing of data analysis in the form of processes of relevance, valence and dominance. The results obtained are 126 answers from research respondents who are considered relevant with 30 answers then the relevant process, the domination process narrows down to 10 answers that have been carried out by the results. Furthermore, the results of the analysis of the psychological conditions felt by Lecturers and the Academic Community of PGRI Madiun University before the implementation of the covid-19 vaccination were that the affective aspect was the first factor that dominated psychological conditions, then the next aspect. cognitive aspect and the most recessive is the conative aspect.